EFEKTIFITAS PROGRAM SABTU CERIA PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KEDIRI - Erlambang, Nanda (FISIP UWP, 2025)
Abstract This scientific research journal discusses the effectiveness of public service policy innovations regarding population document issuance services by the Population and Civil Registration Service of Kediri Regency with its program, namely one day closer (sahaja kekat). In the Sahaja Lekat program, extra time services are also provided, namely Cheerful Saturdays, this program provides an opportunity for people in Kediri Regency to process population documents on Saturdays in 26 sub-districts in the Kediri Regency area. Since it was launched on March 15 2021, the Sahaja Lekat program has received an award from the Ombudsman of the Republic of Indonesia in 2023 and 2024 for public service compliance from the performance of the Kediri district government. The results of this research show that public services in the Sahaja Lekat program have been implemented well, however in the field there are still several problems identified, such as the Saturday Cheer program not being able to provide services for correcting birth certificate data and having to come to the office during working hours and days, network maintenance is down. So the Saturday Cheer program is finally on holiday, and the service for repairing data on death certificates and birth certificates that are damaged or lost and reissued takes a long time, namely 3 days to 1 week. From the description of implementation and problems in the Sahaja Sticky and Saturday Cheerful programs, analysis is needed to understand the effectiveness of public service innovation in the field of publishing population data.